2013
DOI: 10.1371/journal.pone.0068995
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Efavirenz versus Nevirapine-Containing Regimens for Treatment of HIV-1 Infection: A Systematic Review and Meta-Analysis

Abstract: IntroductionThere is conflicting evidence and practice regarding the use of the non-nucleoside reverse transcriptase inhibitors (NNRTI) efavirenz (EFV) and nevirapine (NVP) in first-line antiretroviral therapy (ART).MethodsWe systematically reviewed virological outcomes in HIV-1 infected, treatment-naive patients on regimens containing EFV versus NVP from randomised trials and observational cohort studies. Data sources include PubMed, Embase, the Cochrane Central Register of Controlled Trials and conference pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 28 publications
5
48
1
Order By: Relevance
“…As seen in adult studies 77, two recent retrospective paediatric cohort studies, in resource‐limited and resource‐rich settings, comparing EFV and NVP showed that EFV was associated with superior virological outcomes 78 73, although in the UK/Ireland CHIPS cohort, the benefit of EFV‐based regimens over NVP‐based regimens in terms of virological failure was very modest after 2 years of therapy 73. In the ARROW trial, a nonrandomized comparison of NNRTI‐ based regimens showed favourable short‐term VL suppression with EFV; however, long‐term suppression depended on age, and was better with EFV in children aged < 10 years, and with NVP in those aged > 10 years 79.…”
Section: Which Art Regimen To Start As First‐line Therapymentioning
confidence: 59%
“…As seen in adult studies 77, two recent retrospective paediatric cohort studies, in resource‐limited and resource‐rich settings, comparing EFV and NVP showed that EFV was associated with superior virological outcomes 78 73, although in the UK/Ireland CHIPS cohort, the benefit of EFV‐based regimens over NVP‐based regimens in terms of virological failure was very modest after 2 years of therapy 73. In the ARROW trial, a nonrandomized comparison of NNRTI‐ based regimens showed favourable short‐term VL suppression with EFV; however, long‐term suppression depended on age, and was better with EFV in children aged < 10 years, and with NVP in those aged > 10 years 79.…”
Section: Which Art Regimen To Start As First‐line Therapymentioning
confidence: 59%
“…Initiating cART earlier in disease is obviously beneficial to patient outcome, but only if the patient remains adherent to the cART with full viral suppression (61). Full viral suppression on first-line cART is achieved in Ͼ85% of treatmentnaive HIV-infected individuals/year in HICs (62)(63)(64), but in LMICs, these rates are less than 80% per year (64)(65)(66). Antiretroviral treatment failure is largely due to poor adherence in subSaharan Africa, but purely behavior-based decisions to stop medications are rare, and with access to medication, adherence rates are similar to those in HICs (64,66).…”
Section: Discussionmentioning
confidence: 99%
“…Full viral suppression on first-line cART is achieved in Ͼ85% of treatmentnaive HIV-infected individuals/year in HICs (62)(63)(64), but in LMICs, these rates are less than 80% per year (64)(65)(66). Antiretroviral treatment failure is largely due to poor adherence in subSaharan Africa, but purely behavior-based decisions to stop medications are rare, and with access to medication, adherence rates are similar to those in HICs (64,66). Thus, poor adherence in LMICs is generally related to limited access to clinical centers, high travel costs, intermittent antiretroviral drug supply, and interruptions of funding programs that provide cART (67).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that taking ART containing nevirapine alongside SR treatment leads to a decreased C max and C min of nevirapine due to interaction with rifampicin. [48][49][50] This notwithstanding, early onset of ART and co-trimoxazole prophylaxis is highly recommended by WHO preliminary guidelines for management of HIV/BU coinfection 51 to build up immunity and to fight opportunistic infections associated with HIV as these could worsen the prognosis of the condition. Here 4/7 BU/HIV coinfected patients did not start with ART treatment within the study period because of unavailability of an ART center within or close to the study center.…”
Section: Discussionmentioning
confidence: 99%